2016
DOI: 10.1002/chem.201602197
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β‐1,4‐Linked Galactan Side‐Chains of Rhamnogalacturonan I

Abstract: The synthesis of linear‐ and (1→6)‐branched β‐(1→4)‐d‐galactans, side‐chains of the pectic polysaccharide rhamnogalacturonan I is described. The strategy relies on iterative couplings of n‐pentenyl disaccharides followed by a late stage glycosylation of a common hexasaccharide core. Reaction with a covalent linker and immobilization on N‐hydroxysuccinimide (NHS)‐modified glass surfaces allows the generation of carbohydrate microarrays. The glycan arrays enable the study of protein–carbohydrate interactions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Welldefined, single-compound oligosaccharides provide the highest resolution possible when characterizing protein-carbohydrate interactions, provided that the binding interactions are sufficiently strong to be detected. This is especially true when a range of structurally related but distinct glycans are available (for examples, see Clausen et al, 2003;Andersen et al, 2016aAndersen et al, , 2016bSchmidt et al, 2015). In the case of LM26 discussed here, it would have been close to impossible to identify the epitope without access to the appropriate and defined linear and branched galactans.…”
Section: Discussion Synthetic Glycan Arrays As a Discovery Platformmentioning
confidence: 97%
See 3 more Smart Citations
“…Welldefined, single-compound oligosaccharides provide the highest resolution possible when characterizing protein-carbohydrate interactions, provided that the binding interactions are sufficiently strong to be detected. This is especially true when a range of structurally related but distinct glycans are available (for examples, see Clausen et al, 2003;Andersen et al, 2016aAndersen et al, , 2016bSchmidt et al, 2015). In the case of LM26 discussed here, it would have been close to impossible to identify the epitope without access to the appropriate and defined linear and branched galactans.…”
Section: Discussion Synthetic Glycan Arrays As a Discovery Platformmentioning
confidence: 97%
“…To determine the structure recognized by LM26, the antibody was used to probe extensive sets of glycan microarrays with assembled sets of synthetic oligosaccharides relating to those found in plant cell wall glycans (Andersen et al, 2016a). The LM26 MAb was found to bind to three structurally related branched versions of oligo-b-1,4-galactosides.…”
Section: Monoclonal Antibody Lm26 Binds Specifically To Phloem Sieve mentioning
confidence: 99%
See 2 more Smart Citations
“…[8] Furthermore, we have previously shown that LM5 does not tolerate β-1,6 branching in order to bind to defined galactans. [12] We were interested in more detailed insight into the binding mode of LM5. From previous work, it was not clear whether the non-reducing end of linear β-1,4-galactans is part of the LM5 epitope.…”
Section: Introductionmentioning
confidence: 99%